Development of Cooperative Learning Activity with Peer Reporting to Promote Peer Acceptance of Lower-secondary Students - Sukom, Nuttareeya; Suraseth, Chutima (An Online Journal of Education, 2023)
The purpose of this research is to 1) develop cooperative learning activities with peer reporting to promote peer acceptance and 2) investigate the effects of cooperative learning activities with peer reporting on promoting peer acceptance of all students in the classroom, including neglected or rejected students. The research process uses design thinking. Beginning with understanding a student’s relationship, defining the problem, learning, and designing cooperative learning activities with peer reporting by interviewing 5 homeroom teachers, 3 teachers, 2 professors, and 5 students. The learning activities were then used with 31 secondary school students. Sociometric techniques were used to collect peer acceptance data. The data were analyzed using inductive analysis and sociometric techniques. The findings were as follows:1) Cooperative learning with peer reporting was an activity that encouraged students to work in groups and allowed students to observe and report positive peer behaviors during group activities. 2) After implementing the cooperative learning activities with peer reporting, the sociometric status of some students in the classroom has changed. The sociometric status of seven students increased, and that of two students decreased. The status of five students who used to be neglected or rejected was improved.